Tawhid’s Therapeutic Potential Against Overthinking and Anxiety in Muslim Societies: Qur’anic, Hadith, Salafi Scholarship - Arba’iniyah Khoirunnisa’; Alphareza Lovina Ramadhanie; Agung Pranoto Kadiatmaja (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research investigates the therapeutic potential of Tawhid (affirming God's absolute oneness) as a Qur'anic and Hadith-based solution for overthinking and anxiety prevalent in contemporary Muslim societies. The study addresses the escalating prevalence of these mental health issues, which affect up to 30% of the population in Muslim-majority countries and are exacerbated by socio-economic pressures and inadequate culturally tailored mental health resources. Utilizing a qualitative Library Research method, the study conducts an in-depth content analysis of primary sources (Qur'an and Hadith) and secondary sources (classical tafsir and Salafi scholarly works). The findings affirm that Tawhid serves as a foundational al-ilaj ar-ruhiy (spiritual therapy) that provides a robust cognitive and emotional framework. The study identifies three core mechanisms derived from Tawhid: Tawhid Rububiyyah (Lordship) combats future anxiety and rumination through reliance on Qadar (Divine Decree) and cultivating Tawakkul (reliance); Tawhid Uluhiyyah (Worship) provides behavioral solutions like Dhikr, which acts as a cognitive soother; and Tawhid Asma’ wa Sifat (Names and Attributes) enhances psychological resources by combating helplessness and guilt rumination through names like Al-Wakil (The Disposer of Affairs) and Al-Ghafur (The Forgiving). Furthermore, specific Islamic strategies such as Tahajud, Dhikr, Tawakkul, and Rida (acceptance of divine decree) are affirmed to promote sakinah (tranquility), aligning the Salafi creedal doctrine with principles of modern cognitive restructuring therapy. The novelty lies in its rigorous, targeted, and holistic analysis through the Salafi scholarly lens, offering a doctrinally sound and psychologically relevant framework for intervention.